Welding Safety Equipment : Design of head protection for welding with a human-centred focus on ergonomics, usability and user experience - Pettersson, Josefin; Kafi, Sara (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
Welding is a process with a long historic background and can be traced back to as early as 425 BCE. Using safety equipment and using it correctly is crucial in order to stay unharmed during welding tasks. The profession is associated with health risks due to the UV-radiation that is transmitted from the metal arc, as well as the fumes and particles formed by the molten metal. However, welding helmets seem to have reached a standardised design where little risk is taken by the manufacturers in order to produce innovative and user-centred products. The helmets that dominate the market today lack proper protection against UV-radiation, fumes and particles and are all generally the same construction-wise. In this master thesis, the goal has been to develop a new design of a welding safety equipment for the head with a focus on ergonomics, usability and user experience (UX). Scania Ferruform in Luleå alerted to ergonomic issues regarding welding helmets and expressed a need for a more user-centred and ergonomic design. The ergonomic issues identified by Scania were primarily related to the limited field of view provided in the contemporary helmets, which forced flexion of the neck in order to see the work piece and weld properly. This flexion, and the static postures associated with the welding profession were accordingly resulting in harmful strain and torque in the neck of the welders. The aim for this master thesis project was to improve the work environment for welders by improving the ergonomic conditions through the design of a new welding safety equipment for the head. To communicate and verify the design, the objective was set as to visualise the new design with rendered images and a physical prototype. Innovation has been lacking in the field of welding helmets since the patent for the modern welding helmet was introduced in the 1930’s. Therefore, the project was carried out through an iterative and human-centred design process with the goal of striving for innovation. By involving both professional and ...